EVALUASI PELAKSANAAN KEGIATAN GUBERNUR BADAN EKSEKUTIF MAHASISWA PERIODE 2019/2020 FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS RIAU - Devi Ramsah Wahyuni Simamora; Titi Maemunaty; Jaspar Jas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrak: This research is motivated by the evaluation of the implementation of the governor's activities so that the problem formulation in this study is whether the Evaluation of the Implementation of the Activities of the Governor Executive Body of the 2019-2020 Student Period at the Faculty of Teacher Training and Education, University of Riau has been well implemented